2023
DOI: 10.1037/men0000426
|View full text |Cite
|
Sign up to set email alerts
|

Traditional masculinity and male violence against women: A meta-analytic examination.

Abstract: Traditional masculinity (TM) is conceptualized as a risk factor for the well-being of men and those around them. Further, TM is often considered a key factor in male violence against women, and the positive association between these two factors has been supported by numerous studies. To quantify this relationship, a meta-analysis was conducted on 57 independent samples (mainly from the United States) from 10,772 respondents, reported in 51 articles between 1992 and 2021. We observed that TM positively correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 70 publications
(97 reference statements)
2
9
0
Order By: Relevance
“…Sexism was more strongly associated with TMI and conformity to masculine norms than it was with gender role stress. These findings are consistent with the results of a previous meta-analysis, according to which, compared to GRC, TMI, and conformity to masculine norms were more strongly associated with attitudes toward violence against women (Krivoshchekov et al, 2023). One explanation could be that the content of Gender-Role Conflict Scales correspond less to scales of sexism than scales of TMI and conformity to masculine norms.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Sexism was more strongly associated with TMI and conformity to masculine norms than it was with gender role stress. These findings are consistent with the results of a previous meta-analysis, according to which, compared to GRC, TMI, and conformity to masculine norms were more strongly associated with attitudes toward violence against women (Krivoshchekov et al, 2023). One explanation could be that the content of Gender-Role Conflict Scales correspond less to scales of sexism than scales of TMI and conformity to masculine norms.…”
Section: Discussionsupporting
confidence: 92%
“…On the one hand, compared to gender role stress, the content of TMI and conformity to masculine norms has a greater overlap with sexism (Schwartz et al, 2016); therefore, one might expect that TMI and conformity to masculine norms would be more strongly associated with sexism than gender role stress would be. This is supported by a recent meta-analysis, which showed that TMI has the strongest and gender role stress has the weakest association with violence against women (Krivoshchekov et al, 2023).…”
Section: Relationship Between Tm and Sexismmentioning
confidence: 59%
See 2 more Smart Citations
“…These findings spotlight the value of considering the influences of paternal anxiety and depression separately from maternal influences, as well as the need to investigate the mechanisms through which fathers' experiences of anxiety and depression impact their children (e.g., via negative parenting behaviors). In a meta-analysis of 57 samples, Krivoshchekov et al (2023a) found that traditional masculinity was positively linked to violent attitudes and behaviors toward women. Moreover, the relationship between traditional masculinity and violent attitudes differed as a function of the type of traditional masculinity: The strongest correlation was for traditional masculinity ideology, followed by conformity to masculine norms, and then gender role conflict.…”
Section: Articles In the Special Issuementioning
confidence: 99%